2013
DOI: 10.1590/s0104-66322013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of phospholipase a1 using a polyvinyl alcohol-alginate matrix and evaluation of the effects of immobilization

Abstract: -The paper presents the synthesis and performance of an immobilized phospholipase A1 with practical application for oil degumming. The polyvinyl alcohol (PVA) had a number of properties indicating this polymer as a good enzyme carrier. The combination with alginate made a macro-porous structure, evidenced by SEM analyses. When the process time in boric acid solution was 30 minutes, the results revealed that beads prepared with 10% (w/v) PVA and 2% (w/v) sodium alginate in 4% (w/v) boric acid and 2% (w/v) calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 27 publications
2
6
0
3
Order By: Relevance
“…These results were possibly due to the porosity of the prepared beads. A high concentration of PVOH and the modified xylan might lead to the high density of physical cross-linking sites, resulting in the formation of small pores on and inside the beads, which probably limits the diffusivity of the substrate (Zhan et al 2013). In contrast, the low concentration of the modified xylan and PVOH may cause a reduction in mechanical strength and the increment of the pore size resulting in enzyme leakage (El-Tanash et al 2011).…”
Section: Optimization For Laccase Immobilization Into the Modified Xymentioning
confidence: 99%
“…These results were possibly due to the porosity of the prepared beads. A high concentration of PVOH and the modified xylan might lead to the high density of physical cross-linking sites, resulting in the formation of small pores on and inside the beads, which probably limits the diffusivity of the substrate (Zhan et al 2013). In contrast, the low concentration of the modified xylan and PVOH may cause a reduction in mechanical strength and the increment of the pore size resulting in enzyme leakage (El-Tanash et al 2011).…”
Section: Optimization For Laccase Immobilization Into the Modified Xymentioning
confidence: 99%
“…PVA effectively improves the stability of immobilized cell beads with a promoted mechanical strength, while SA improves the surface properties of immobilized cell beads to keep from the tendency to agglomeration. Therefore, SA-PVA hydrogel can be regarded as a proper material for cell immobilization (Zhan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies by Singh et al [6], synthetic organic carriers have gained a lot of attention mainly due to their effectiveness in protection from harsh environments such as high temperature or pressure. Furthermore, Zhan et al [7] indicated that sodium alginate-PVA based matrices boast excellent properties for parameters such as reusability and stability. PVA contributes to the improvement of durability, whereas sodium alginate is said to improve surface properties such as diffusibility and porosity, which in turn increases interaction.…”
Section: Resultsmentioning
confidence: 99%